Changes in longer consultations for children in general practice. Issue 4 (21st March 2013) - Freed, Gary L; Spike, Neil A; Sewell, Jillian R; Moran, Lauren M; Britt, Helena; Valenti, Lisa; Brooks, Peter
<x xml:space="preserve">Abstract</x> Aim To determine if the duration of general practitioner (GP) consultations, or the proportional distribution of item numbers associated with longer consultations, with children has changed in association with the demographic changes in Australia. Method Secondary data analysis of Medicare claims from 1996 to 2010, which were stratified by patient age and visit type as designated by billing item number, and of the Bettering the Evaluation of Care and Health (BEACH) database was conducted. The Medicare data that were analysed were changes in overall proportion and absolute numbers of longer consultations for children from 1996 to 2010, while the BEACH data that were analysed were changes in the average duration of visits for children and the proportion of visits by children for chronic conditions. Results Despite the increase in the population of children, and the increasing numbers of children with chronic illness, the absolute number of longer consultations for children has decreased over the time period studied. Further, the proportion of all longer consultations that are being provided to children has diminished. For those consultations that do occur, the GPs are not spending any more time with children in 2010 than they did in consultations in 2000. Conclusions There have been significant changes in the patterns of longer consultations provided to children by GPs. Efforts to ensure that children receive primary care for chronic conditions and preventive care must now take on a greater urgency for the health‐care system.